Determination of antioxidant activity and total phenols of pequi (Caryocar brasiliense Camb.) (Research, Society and Development, 2020)
Natural antioxidants in fruits draws enormous attention from the scientific community due to their role in the prevention and control of diseases associated with oxidative stress. The aim of this study was to evaluate the antioxidant activity of different concentrations of the aqueous extract obtained from the pequi pulp, using the combination of different methodologies. From 4 % (g/dL) of such extract, determined the concentration of total phenolic compounds and the in vitro analysis of the antioxidant potential were determined by assays of the sequestering activity of the radical 2,2-diphenyl-1-picryl-hydrazil (DPPH) and metal reducing power. For the ex vivo evaluation, the capacity of inhibiting lipid peroxidation, estimated by the formation of substances reactive to thiobarbituric acid, was determined in rat brain homogenate. The total phenolic content was 2.22 ± 0.045 g of tannic acid equivalents/100 g. DPPH test showed that all fractions of the processed samples had activity at different concentrations. Regarding the inhibition of lipid peroxidation, the Tukey test showed a reduction in levels, with a significant difference (p